Quantitative evidence of the occurrence of a motivational dip in language learning in Year 7. Issue 5 (20th October 2019) - Deckner, Sebastian Ephraim
ABSTRACT: This article presents selected findings from a study of the motivation of UK school pupils to learn a modern foreign language. The study involved 345 year 7 pupils (i.e. 11–12-year-old children) learning either French or German in a large inner-city school based in an urban area in central England. Anecdotal evidence suggested a widespread decrease in motivation for modern language learning during the course of year 7. The purpose of the study was to seek evidence substantiating or refuting the hypothesis of a motivational dip and to investigate factors that might account for any changes in motivation. Two questionnaires were used to collect data in the autumn of 2007 and spring/summer of 2008. The data were analysed employing quantitative methodology and the findings suggested that there was indeed evidence of an overall trend towards demotivation, though when data were analysed in class groups very different profiles emerged. Contrary to suggestions in the literature and wider society the drop in motivation could not be explained through the impact of individual factors, such as the teacher, nor did any combination of factors seem to suggest predictable outcomes. However, reference to Dörnyei's [2005. The Psychology of the Language Learner: Individual Differences in Second Language Acquisition . Mahwah, NJ: Lawrence Erlbaum; 2009a. The L2 motivational self system. In Motivation, Language Identity and the L2 Self, ed. Z. Dörnyei and E. Ushioda, 9–42. Bristol: Multilingual Matters] L2 Motivational Self System could be made in order to provide a careful interpretation of the trends observed in the data.